Histopathological evaluation of the effect of vitamin E on rat kidney after complete unilateral urethral obstruction - G.h Mousavi; D Mohajeri; A Agebati Maleki; R Kafash Elahi; M Neshat; H Khayat Nouri (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2009)
Vitamin E is an important antioxidant, which plays a vital role in preventing free radical induced reperfusion injuries. Any disorder in the normal urinary flow is termed obstructive nephropathy which could ultimately lead to hydronephrosis, atrophy and complete impairment of renal function. The aim of this study was to determine the effect of vitamin E on renal tissue following complete unilateral urethral obstruction in the rat. In this experimental study, 30 adult male Sprague-Dawley rats were randomly divided into three groups each containing 10 rats. The first group was considered as the control group. Following Unilateral urethral obstruction (UUO), rats in the second group received olive oil intraperitoneally for 15 days starting one day before surgery. Group three rats were given 50 Iu/kg of Vitamin E intraperitoneally for 15 days starting one day before unilateral obstruction (UUO-Vit E). Rats were euthanized at day 14 after surgery for histopathological evaluation and their left kidneys were collected and fixed in formalin and stained with Hematoxylen and Eosin, Trichrome-masson and Periodic Acid Schiff techniques. Histopathological evaluation revealed dilation of the Bowman’s capsule, severe glomerular and tubular atrophy, periglomerular sclerosis, interstitial infiltration of mononuclear cells, severe diffuse tubular degeneration, epithelial thickening of Bowman’s capsule, perivascular edema, interstitial fibrosis, hemorrhage and sub capsular fibrosis in the UUO group. Vitamin E administration in the UUO-Vit E group significantly decreased renal tissue lesions and fibrosis. The result of the present study indicated that urethral obstruction leads to severe renal fibrosis and tissue damage and concurrent administration of Vitamin E decreases tissue lesions and fibrosis resulting from the obstruction.